Legal Protection of Children as Perpetrators or Victims of Criminal Acts Whose Identities Are Revealed in Court Decisions - Larassati, Aura Dara; Elviandri, Elviandri (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
This research aims to determine the legal provisions regarding judge's decisions that reveal the child's identity. Understand the legal implications of disclosing the identity of child perpetrators or victims of criminal acts in court decisions regarding children's rights. The approach method applied in this research is a normative method, which includes research into the literature studied. Using a statutory approach regarding the protection of children's identities in the criminal justice system, while an empirical approach is used to study the implementation of these regulations in judicial practice, especially in decision number 14/Pid.Sus- Anak/2021/PN Srg. The legal materials used consist of primary legal materials and secondary legal materials. The results of this research are that protecting children in conflict with the law is the state's obligation to protect every right they have. This obligation is aimed at the best interests of the child and prevents the child from being mistreated by any party. One of these rights is that it is not permissible to publish a child's identity in conflict with the law, whether in print/electronic media. A court decision that reveals a child's identity can be considered a criminal offense because it violates legal provisions regarding the confidentiality of a child's identity which must be protected. One of the main principles of child protection is the best interests of the child. In this case, the judge is also obliged to keep the identity of the child as the perpetrator of the crime secret during the trial process. In conflict with the law, children's identities must be kept confidential, both in print and electronic media. Children are the nation's generation and figures who greatly influence the continuity of the nation's life, where they have rights that must be protected, respected and fulfilled. The confidentiality of the identity of children in conflict with the law is one of the rights given to them to protect their reputation.